Investigating the relationship between online information seeking and translation performance among translation students: The mediating role of translation self-efficacy - Lu, Sha; Xiangling, Wang; Shuya, Ma (Frontiers in Psychology, 2022)
The widespread use of online information resources by translation students has motivated an increasing number of researchers to investigate the relationship between online information seeking and translation performance. However, these studies mainly address the direct effect of online information seeking on translation performance, thus failing to explore and identify the internal psychological mechanisms. This study, therefore, explores the mediating role of translation self-efficacy in the relationship between online information seeking and translation performance. A total of 314 translation students in China completed questionnaires on online information seeking and translation self-efficacy, and translation performance was measured by assessing the quality of a translation task given to them. Results showed that translation self-efficacy partially mediated the association between online information seeking and students’ translation performance. These findings can contribute to our understanding of the role that translation self-efficacy plays in information seeking behaviors and the emotional states of translation students in translator training.